The use of the peak-clipping method for energy management in households with energy storage equipment. (2nd April 2020) - Chang, Chien-Kuo; Lee, Sheng-Hung; Wu, Ruay-Nan; Lee, Chung-Heng; Chang, Jyun-Hui
ABSTRACT: The purpose of this paper is to investigate how energy storage systems should be used to improve the load factor of a residential power grid, thus equalizing the hourly power consumption of these grids, which will help to mitigate power supply difficulties during load peaks. There are two methods represented in this paper. First, the schedule optimization method using continuous quadratic programming to solve each point in time for optimal objects according to forecast load. Second, the "peak-clipping" method proposed in this paper is much simpler, as it does not require load predictions and simply corrects the predicted cutoff lines based on the errors of each run. As a result, the schedule optimization method could theoretically improve this load factor up by to 65.7%, but it was only increased by 50.4% actually in real-time. The peak-clipping method could theoretically improve load factor up to 64.5%, and the simulation indicates that load factor improved by 56.7%. It is shown that the peak-clipping scheme is relatively simple and highly effective, which makes it straightforward to implement in various control devices or system platforms.